2022
DOI: 10.1016/j.cegh.2022.100971
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of clinical outcomes between vaccinated and vaccine-naive patients of COVID-19, in four tertiary care hospitals of Kerala, South India

Abstract: The problem considered This multi-centric study analyzed data of COVID-19 patients and compared differences in symptomatology, management, and outcomes between vaccinated and vaccine-naive patients. Methods All COVID-19 positive individuals treated as an in-or out-patient from the 1 st March to 15 th May 2021 in four selected study sites were considered for the study. Treatment details, symptoms, and clinical course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 7 publications
2
9
0
1
Order By: Relevance
“…Balachandran et al [14] compared outcomes among vaccinated and unvaccinated in a retrospective study in South Kerala, India, and reported 4.21 timer higher odds of mortality among unvaccinated patients; similar to results reported in our study. They also reported a higher prevalence of respiratory and neurological symptoms in vaccinated patients; however, no such findings were noted in our study population.…”
Section: Discussionsupporting
confidence: 90%
“…Balachandran et al [14] compared outcomes among vaccinated and unvaccinated in a retrospective study in South Kerala, India, and reported 4.21 timer higher odds of mortality among unvaccinated patients; similar to results reported in our study. They also reported a higher prevalence of respiratory and neurological symptoms in vaccinated patients; however, no such findings were noted in our study population.…”
Section: Discussionsupporting
confidence: 90%
“…Major symptoms of COVID-19 are cough, breathlessness, fever, loose stool, and haemoptysis; which were reduced in the patients vaccinated with a single dose and fully vaccinated as compared to the unvaccinated patients. A multi-centric study with a sample size of 1446 patients conducted in four tertiary care hospitals in Kerala, South India, showed that severity of infection, duration of hospital stays, need for ventilation, and death were significantly less among vaccinated patients vs. unvaccinated patients [ 78 ]. Similarly, another retrospective cohort study conducted in Brazil reported the reduction in hospital stays and the need for mechanical ventilation in infected health care workers vaccinated with Oxford-AstraZeneca (ChAdOx1) or Corona vac [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 14 studies were included to analyze the effect of age. We found no statistical difference in the age of the two groups (SMD = 0.085, 95% CI = À0.073-0.189, p = 0.388, 12 Case-control study 346 1100 ☆☆☆ ☆☆ ☆☆ 7☆ Wi 18 Case-control study 142 20 ☆☆ ☆☆ ☆☆ 6☆ Tenforde 13 Case-control study 314 1669 ☆☆☆ ☆☆ ☆☆ 7☆ Hsu 19 Case-control study 85 85 ☆☆ ☆☆ ☆☆☆ 7☆ Blanquart 20 Case-control study 724 5459 ☆☆☆ ☆☆ ☆☆ 7☆ Bollineni 21 Case-control study 14 56 ☆ ☆☆ ☆☆☆ 6☆ Marincu 22 Case-control study 62 62 ☆☆ ☆☆ ☆☆☆ 7☆ Wolff 23 Case-control study 260 507 ☆☆☆ ☆☆ ☆☆☆ 8☆ Kalligeros 24 Case-control study 91 824 ☆☆☆ ☆☆ ☆☆☆ 8☆ Fragoulis 25 Cohort study 101 60 ☆☆☆ ☆☆ ☆☆☆ 8☆ Trunfio 26 Cohort study 55 110 ☆☆☆ ☆☆ ☆☆ 7☆ Safdar 27 Cohort study 45 65 ☆☆☆ ☆☆ ☆☆☆ 8☆ Bouton 28 Cohort study 96 329 ☆☆ ☆☆ ☆☆☆ 7☆ Bosch 29 Case-control study 126 839 ☆☆ ☆☆ ☆☆☆ 7☆ Christensen 30 Case-control study 3346 13,619 ☆☆☆ ☆☆ ☆☆☆ 8☆ Yu 31 Case-control study 23 50 ☆☆☆ ☆☆ ☆☆☆ 8☆ Bayhan 32 Case-control study 38 190 ☆☆☆ ☆☆ ☆☆☆ 8☆ Kustin 33 Case-control study 396 396 ☆☆ ☆☆ ☆☆ 6☆ Toda 34 Case-control study 11 15 ☆☆☆ ☆☆ ☆☆☆ 8☆ Tian 4 Case-control study 88 41 ☆☆☆ ☆☆ ☆☆☆ 8☆ Sayed 35 Case-control study 50 70 ☆☆☆ ☆☆ ☆☆☆ 8☆ Lee 36 Case-control study 174 587 ☆☆☆ ☆☆ ☆☆☆ 8☆ Luo 37 Case-control study 484 1782 ☆☆☆ ☆☆ ☆☆ 7☆ Puhach 38 Case-control study 139 245 ☆☆ ☆☆ ☆☆ 6☆ Whittaker 39 Case-control study 716 2487 ☆☆☆ ☆☆ ☆☆☆ 8☆ Sanghavi 40 Case-control study 149 478 ☆☆☆ ☆☆ ☆☆☆ 8☆ Butt (1) 41 Case-control study 250 250 ☆☆☆ ☆☆ ☆☆☆ 8☆ Butt (2) 42 Case-control study 456 456 ☆☆☆ ☆☆ ☆☆☆ 8☆ Spiera 43 Case-control study 88 2317 ☆☆ ☆☆ ☆☆☆ 7☆ Baltas 44 Case-control study 119 476 ☆☆☆ ☆☆ ☆☆ 7☆ John 45 Case-control study 254 508 ☆☆ ☆☆ ☆☆ 6☆ Jacobson 46 Case-control study 189 471 ☆☆ ☆☆ ☆☆ 6☆ Estofolete …”
Section: Ageunclassified
“…According to some studies, vaccinated patients have lower risk factors for hospitalization, infectious diseases, and death. 12,13 However, other studies have indicated that VOCs can evade antibody responses 14 and there is a similar Cycle threshold (Ct) value 15 between infected individuals who have not been vaccinated and have been vaccinated.…”
Section: Introductionmentioning
confidence: 99%